The Current State of The Problem of Technological Entrepreneurship - Anna N. ZAKHAROVA; Tamara V. TALANOVA; Tatyana A. LAVINA; Anna S. GROMOVA; Anna N. ERYGINA; Alena Yu. NIKOLAEVA (Communications of International Proceedings, 2023)
The article analyzes foreign and domestic research on the current state of the problem of technological entrepreneurship, including student entrepreneurship. Differentiation of research approaches on the problems of student technological entrepreneurship research was carried out.  The experience of programs and projects to support and develop student technological entrepreneurship abroad and in Russia is analyzed.
Keywords: student technological entrepreneurship; youth technological entrepreneurship; innovation activity